2008
DOI: 10.1592/phco.28.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Dosage Titration of Levetiracetam in Children

Abstract: Rapid dosage titration of levetiracetam is feasible and well tolerated in children who require rapid escalation to therapeutic doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Strikingly, dizziness and irritability have a similar frequency at all drug doses. M a n u s c r i p t Even though the reasons for these atypical findings are not clear, the lack of a dose-effect relationship for several AEs can explain the clinical profile of LEV, which is considered a drug with a very good tolerability [1,3] and which can be titrated very fast without severe consequences [40].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Strikingly, dizziness and irritability have a similar frequency at all drug doses. M a n u s c r i p t Even though the reasons for these atypical findings are not clear, the lack of a dose-effect relationship for several AEs can explain the clinical profile of LEV, which is considered a drug with a very good tolerability [1,3] and which can be titrated very fast without severe consequences [40].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…One prospective study of levetiracetam (n = 31) found higher rates of adverse effects in patients taking .45 mg/kg/day,3 whereas two other retrospective chart reviews (n = 3219 and n = 155) did not find that tolerability of levetiracetam is dose-dependent. Rapid titration of levetiracetam (1–14 days) can be well tolerated, although adverse effects were observed in 12%–22% of subjects 10,75…”
Section: Safety and Tolerabilitymentioning
confidence: 99%